Impacting Technology on Employees' Job Performance: A Case Study of Commercial Banks in Vietnam - Hien, Lam Thanh; Tam, Phan Thanh (Journal of Applied Data Sciences, 2025)
Technology is driving rapid transformation in the way people work. Many banks have caught up by introducing technology into their operations and training their personnel to use technology to optimize work productivity. Besides, employee technology competency is one of the most critical issues for organizations, helping them maintain a competitive position in the market. Therefore, the research aimed to measure critical factors impacting on bank employees' job performance and policy recommendations. The methodology of this study applied a structural equation model consisting of five factors: knowledge, attitude, hard skills, soft skills, and technology, and examined the impact of the above factors on tasks, context, and job performance. Data were collected from 900 employees working for 40 branches at 15 commercial banks in Vietnam and processed using SPSS 20.0 and Amos software. After testing the scale’s reliability, convergence, and discrimination, the study's findings showed that the critical factors of knowledge, attitude, skills, and technology positively impact task, contextual, and job performance. In addition, the originality of this research includes the introduction of technological factors into the model, a new factor of the banking industry in the digital transformation period in Vietnam. Based on the results of testing the research model, the authors provided empirical evidence that the career competency framework includes critical factors: knowledge, attitude, skills, and technology that positively impact task performance, contextual performance, and employee job performance. The practical implications of the article proposed management implications to help employees, managers, and policymakers improve employees' knowledge, attitudes, and skills, which play an essential role in performing their duties, and improving job performance in digital competency is one of the required skills in the banking industry.